Clinical features and prognosis of the adult patients positive for both N-methyl-d-aspartate receptor and myelin oligodendrocyte glycoprotein antibodies - Ma, Yifang; Liu, Binting; Ci, Xiaojiao; Lu, Jie (Frontiers in Immunology, 2025)
IntroductionThe coexistence of the MOG antibody (MOG-ab) and NMDAR antibody (NMDAR-ab), which is known as the MOG-ab and NMDAR-ab overlapping syndrome (MNOS), is the most common in overlapping syndromes of neural autoantibodies. The study aimed to analyze the clinical features and outcomes in adult patients suffering from MNOS and investigate the mechanisms of the disorder.MethodsAdult patients suffering from MNOS admitted to the Affiliated Brain Hospital of Nanjing Medical University from 2020 to 2024 was systematically reviewed. The clinical symptoms, laboratory data, imaging results, treatments, and prognoses were evaluated. Moreover, the clinical data of MNOS patients were compared with those of anti-NMDAR encephalitis (anti-NMDARE) patients and MOG antibody-associated disorders (MOGAD) patients, respectively.ResultsThe study identified 23 adult patients of MNOS. The study cohort comprised 20 males (86.96%) and 3 females (13.04%), with a mean age of onset of 36.17 ± 11.21 years. Prodromal infection was observed in 9 patients (39.13%). Sleep disorder was most common (69.57%), followed by psychiatric disorder and cognitive impairment (65.22%), consciousness disorder (60.87%), seizures (56.52%), speech disorder (39.13%), and headache (39.13%). Radiologically, 5 patients (21.74%) had damage to the cerebral cortex and basal ganglia. 4 patients (17.39%) had damage to the brainstem. All patients received first-line immunotherapy, and 16 (69.57%) of these patients received second-line treatment and long-term immunotherapy. Across 23 clinical attacks, the median modified Rankin Scale score (mRS) improved from 3 [interquartile range (IQR): 3,4] pre-treatment to 1 (IQR: 0,1) post-treatment. Relapses occurred in 6 patients (26.09%). We selected 51 adult patients with anti-NMDARE and 30 adult patients with MOGAD who had onset during the same period as the control groups. In terms of gender, psychiatric disorder, and brainstem involvement, there were significant differences between the anti-NMDARE group and the MNOS group. Regarding visual impairment, limb weakness, deep white matter lesion, and QAlb, differences were observed between the MOGAD group and the MNOS group.DiscussionWhen atypical clinical symptoms and imaging results appear, clinicians should consider the possibility of antibody overlap. During anti-NMDARE relapse, attention should be paid to whether anti-MOG antibodies are co-present.